Evaluation of Retinal Layers Changes in Early Diabetic Retinopathy (Annals of Medical Research, 2021)
Aim: To evaluate the neuronal changes in diabetic patients and investigate the importance of these changes in early diabetic retinopathy determination.Material and Methods: Two hundred eyes of 100 patients were included in this study: 50 diabetics without diabetic retinopathy (group 1) and 50 controls (group 2). Exclusion criteria were macular edema, proliferatif diabetic retinopathy, refractive error >+/-6 diopters, glaucoma, uveitis, ocular surgery. HbA1c levels and duration of diabet were recorded in group 1. Full ophtalmic examination, stereoscopic fundus photography, and optical cohorence tomography (OCT) were taken after adequate dilatation. Mean macular thickness (MT), ganglion cell layer+iner plexiform layer superior, and inferior quadran (GCC/IPLs,i) thickness, inner nucleer layer+outer plexiform layer (INL/OPL) thickness were calculated for each group.Results: Of the 100 patients, 50 were diabetic patients (46 males, 54 females). Of the 50 healthy subjects, 46 were males and 54 were females. The mean age of the diabetics was 56,85 (±6,09) years; this was 57,19 (±5,045) years for the control group patients. Visual acuity was 0,97±0,15 in group 1 and 0,98±0,12 in goup 2, while the mean intraoculer pressure was 13,54±2,8 in group 1 and13,68±3,4 in group 2. The mean HbA1c levels were 7,2±1,9 and mean duration of diabet was 11,8±1,9 in group 1. The GCC/IPL was thinner and INL/OPL was thicker in group 1 but there was no significant difference between the two groups (p=0,830, p=0,372, p=0,051).Conclusions: We observed decreased thickness GCC+IPLs,i and increased INL/OPL in group1 but there was no significant difference between the two groups . The GCC/IPL and INL/OPL layering by OCT did not prove to be a useful tool alone to diagnose neuronal damage in early diabetic retinopathy.Keywords: Diabetic Retinopaty; Retinal Layer; Optical Cohorence Tomography.